A positive electrode of a ternary lithium ion battery, a battery and a preparation method of the positive electrode
Patent Information
- Application Number
- CN202511164129.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-19
- Publication Date
- 2026-10-30
AI Technical Summary
此外,在充放电过程中相变体积变化导致结材料开裂,导致新鲜表面的暴露,消耗电解液,增大正极侧阻抗,恶化电性能
[0028]本发明中,正极包括:Li(NiaCobMnc)xM1-xO2;M为Al和Sb。在正极材料中引入高扩散性、离子半径小的Al元素实现体相掺杂,更高的Al-O键能稳定材料体相结构,提升循环性能。在正极材料中引入低扩散性、离子半径大的Sb元素,一方面缓解材料在充放电过程中由于相变应力集中导致的颗粒破裂现象;另一方面Sb在颗粒表面的富集稳定材料表面晶格氧,抑制表面结构衰减,同时降低表面活性,抑制颗粒生长,制备出颗粒小的正极材料,改善材料循环性能。且Al、Sb共掺杂协同作用提高材料体相和表面金属氧键键能,抑制晶格氧的释放,提升材料热稳定性。
Smart Images

Figure CN123017872A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the technical field of batteries, and in particular to a positive electrode for a ternary lithium-ion battery, a ternary lithium-ion battery, and a method for preparing the positive electrode for a ternary lithium-ion battery. Background Technology
[0002] Lithium-ion batteries have advantages such as high energy density, long cycle life, and no memory effect, and are widely used in various portable electronic devices and vehicles.
[0003] Among them, ternary lithium-ion batteries have attracted increasing attention due to their high energy density, high operating voltage, and good kinetic performance. Cathode materials play a crucial role in the electrochemical performance of batteries and are an important component of lithium-ion batteries. Therefore, the development of cathode materials with high structural stability, high specific capacity, and good kinetics is of great significance to the development of lithium-ion batteries.
[0004] Ternary high-nickel materials have a low proportion of inactive elements Mn and Co in their stable structure, resulting in significant structural degradation during cycling. Furthermore, the phase transition volume change during charge and discharge causes cracking in the junction material, exposing fresh surfaces, consuming electrolyte, increasing positive electrode impedance, and deteriorating electrical performance. High-nickel cathodes have a high Ni content, making it easier for lattice oxygen to escape from their surface during charging, leading to poor thermal stability. Summary of the Invention
[0005] In view of the above problems, a ternary lithium-ion battery cathode, a ternary lithium-ion battery, and a method for preparing the cathode of a ternary lithium-ion battery are proposed to overcome or at least partially solve the above problems. By introducing Al and Sb into the ternary cathode, bulk and surface co-doping is achieved to obtain a cathode material with a highly stable core-shell structure. Bulk doping of Al introduces Al-O bonds with higher bond energy, thereby improving the bulk structural stability of the material. The introduction of Sb can adjust the microstructure of the material, alleviate the stress concentration caused by the shrinkage and expansion of the phase change material, and suppress the generation of microcracks. In addition, the enrichment of Sb on the material surface can stabilize the lattice oxygen on the cathode surface, suppress surface structure decay, and improve the thermal stability of the material in the high delithiation state.
[0006] A positive electrode for a ternary lithium-ion battery, the positive electrode comprising:
[0007] Li(Ni a Co b Mn c ) x M 1-x O 2;
[0008] Where 0.9≤x<1, a+b+c=1, M represents Al and Sb, and the molar ratio of Al to Sb is 0.7-1.5.
[0009] The present invention also provides a ternary lithium-ion battery, wherein the positive electrode of the ternary lithium-ion battery is as described above.
[0010] This invention also provides a method for preparing the positive electrode of a ternary lithium-ion battery, the method comprising:
[0011] Ternary precursors are generated based on Ni, Co, and Mn sources;
[0012] The ternary precursor was mixed with Li, Al, and Sb sources and then sintered to obtain the cathode material: Li(Ni) a Co b Mn c ) x M 1-x O2; where 0.9≤x≤1, a+b+c=1, M is Al and Sb, and the molar ratio of Al to Sb is 0.7-1.5;
[0013] The positive electrode is prepared according to the positive electrode material of the positive electrode.
[0014] Optionally, the step of generating the ternary precursor based on the Ni source, Co source, and Mn source includes:
[0015] After uniformly mixing the Ni source, Co source, Mn source, precipitant and complexing agent, the pH was adjusted to 10-13, and the mixture was stirred at 50℃-80℃ for 1-2 hours to obtain the first solution.
[0016] After aging the first solution for 10-24 hours, it is filtered and dried to obtain the ternary precursor.
[0017] Optionally, the Al source is either aluminum oxide or aluminum hydroxide.
[0018] Optionally, the Sb source is one of antimony oxide, antimony sulfate, and antimony acetate.
[0019] Optionally, the molar ratio of the ternary precursor:Li:Al:Sb is:
[0020] 1:(1-1.02):(0.001-0.0015):(0.0015-0.001).
[0021] Optionally, the precipitant is one of ammonium carbonate, ammonium bicarbonate, sodium carbonate, and sodium hydroxide;
[0022] The complexing agent is one of ammonia, ammonium bicarbonate, and citric acid.
[0023] Optionally, the Ni source is one of nickel nitrate, nickel sulfate, and nickel chloride;
[0024] The Co source is one of cobalt nitrate, cobalt sulfate, and cobalt chloride;
[0025] The Mn source is one of manganese nitrate, manganese sulfate, or manganese chloride.
[0026] Optionally, the Li source is one of lithium hydroxide, lithium carbonate, and lithium acetate.
[0027] The present invention has the following advantages:
[0028] In this invention, the positive electrode includes: Li(Ni) a Co b Mn c ) x M 1-x O2; M represents Al and Sb. Introducing Al, a highly diffusive element with a small ionic radius, into the cathode material achieves bulk doping. The higher Al-O bond energy stabilizes the bulk structure of the material, improving cycle performance. Introducing Sb, a low-diffusive element with a large ionic radius, into the cathode material alleviates particle breakage caused by phase transformation stress concentration during charge and discharge. Furthermore, Sb enrichment on the particle surface stabilizes lattice oxygen, inhibiting surface structure decay and reducing surface activity, thus suppressing particle growth and producing small-particle cathode materials, improving cycle performance. The synergistic effect of Al and Sb co-doping increases the bond energy of both the bulk and surface metal-oxygen bonds, suppressing lattice oxygen release and enhancing the material's thermal stability. Attached Figure Description
[0029] To more clearly illustrate the technical solution of the present invention, the accompanying drawings used in the description of the present invention will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0030] Figure 1 This is a flowchart illustrating the steps of a method for preparing the positive electrode of a ternary lithium-ion battery according to an embodiment of the present invention. Detailed Implementation
[0031] To make the above-mentioned objects, features, and advantages of the present invention more apparent and understandable, the present invention will be further described in detail below with reference to the accompanying drawings and specific embodiments. Obviously, the described embodiments are only some, not all, of the embodiments of the present invention. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort are within the scope of protection of the present invention.
[0032] In one embodiment of the present invention, a positive electrode for a ternary lithium-ion battery is provided, which may include:
[0033] Li(Ni a Co b Mn c ) x M 1-x O 2;
[0034] Where 0.9≤x<1, a+b+c=1, M represents Al and Sb, and the molar ratio of Al to Sb is 0.7-1.5.
[0035] For example, the ternary lithium-ion battery can be a ternary high-nickel lithium-ion battery or other ternary lithium-ion batteries, and the embodiments of the present invention do not limit it.
[0036] For example, Al and Sb can replace some of Ni, Co, and Mn, forming Al-O and Sb-O bonds. Introducing Al, a highly diffusive element with a small ionic radius, into the cathode material enables bulk doping. The higher Al-O bond strength stabilizes the bulk structure of the material, improving cycle performance. Conversely, introducing Sb, a low-diffusion element with a large ionic radius, into the cathode material, on the one hand, modulates the material's microstructure, mitigating particle breakage caused by phase transformation stress concentration during charge and discharge; on the other hand, Sb enrichment on the particle surface stabilizes lattice oxygen, inhibiting surface structure decay, reducing surface activity, suppressing particle growth, and producing small-particle cathode materials, thus improving cycle performance. Furthermore, the synergistic effect of Al and Sb co-doping increases the bond energy of both the bulk and surface metal-oxygen bonds, suppressing lattice oxygen release and enhancing the material's thermal stability.
[0037] In another embodiment of the present invention, a ternary lithium-ion battery is also provided, wherein the positive electrode of the ternary lithium-ion battery can be the positive electrode of the ternary lithium-ion battery mentioned in the above embodiments.
[0038] In another embodiment of the present invention, a method for preparing the positive electrode of a ternary lithium-ion battery is also provided, such as... Figure 1 The diagram shows a flowchart of the steps involved in preparing the positive electrode of a ternary lithium-ion battery according to an embodiment of the present invention.
[0039] like Figure 1 As shown, the preparation method may include the following steps:
[0040] Step 101: Generate a ternary precursor based on the Ni source, Co source and Mn source.
[0041] In this embodiment of the invention, a ternary precursor can be generated first using a Ni source, a Co source, and a Mn source; for example, the ternary precursor can be nickel-cobalt-manganese hydroxide Ni. a Co b Mn c(OH)2.
[0042] Step 102: The ternary precursor is mixed with Li source, Al source and Sb source and then sintered to obtain the cathode material: Li(Ni) a Co b Mn c ) x M 1-x O2; where 0.9≤x≤1, a+b+c=1, M is Al and Sb, and the molar ratio of Al to Sb is 0.7-1.5.
[0043] After obtaining the ternary precursor, it can be mixed with Li, Al, and Sb sources, and then the mixture can be sintered to obtain the cathode material for the ternary lithium-ion battery as mentioned in the previous embodiments. The sintering temperature can be 600℃~800℃, the heating rate can be 2-10℃ / min, the sintering atmosphere is pure oxygen, and the sintering holding time is 5h~20h.
[0044] The positive electrode material can be as follows:
[0045] Li(Ni a Co b Mn c ) x M 1-x O2; where 0.9≤x≤1, a+b+c=1, and M represents Al and Sb.
[0046] For example, the ternary precursor can be ball-milled and mixed uniformly with Li, Al, and Sb sources, and then the mixture can be sintered to obtain the cathode material for the ternary lithium-ion battery as mentioned in the foregoing embodiments. The ball milling speed can be 1000 rpm to 5000 rpm, and the mixing time can be 5 min to 20 min.
[0047] In some feasible embodiments, the Al source is either aluminum oxide or aluminum hydroxide.
[0048] In some feasible embodiments, the Sb source is one of antimony oxide, antimony sulfate, or antimony acetate.
[0049] In some feasible embodiments, the Li source is one of lithium hydroxide, lithium carbonate, and lithium acetate.
[0050] For example, the molar ratio of the ternary precursor:Li:Al:Sb can be:
[0051] 1:(1-1.02):(0.001-0.0015):(0.0015-0.001).
[0052] Step 103: Prepare the positive electrode according to the positive electrode material.
[0053] After obtaining the cathode material, a cathode as mentioned in the above embodiments can be prepared based on the cathode material, and a ternary lithium-ion battery can be further prepared based on the cathode. The embodiments of the present invention do not limit this.
[0054] In one embodiment of the present invention, step 101 can be implemented in the following manner:
[0055] After uniformly mixing the Ni source, Co source, Mn source, precipitant and complexing agent, the pH was adjusted to 10-13 and stirred at 50℃-80℃ for 1-2 hours to obtain the first solution. After aging the first solution for 10-24 hours, it was filtered and dried to obtain the ternary precursor.
[0056] In some feasible embodiments, the Ni source, Co source, Mn source, precipitant and complexing agent can be mixed evenly first; for example, the precipitant can be one of ammonium carbonate, ammonium bicarbonate, sodium carbonate and sodium hydroxide; the complexing agent can be one of ammonia water, ammonium bicarbonate and citric acid.
[0057] The Ni source can be one of nickel nitrate, nickel sulfate, or nickel chloride; the Co source can be one of cobalt nitrate, cobalt sulfate, or cobalt chloride; and the Mn source can be one of manganese nitrate, manganese sulfate, or manganese chloride.
[0058] After uniformly mixing the Ni source, Co source, Mn source, precipitant, and complexing agent in a solvent (e.g., water), the pH of the solution can be adjusted to 10-13. Then, the solution is stirred at 50℃-80℃ for 1-2 hours to obtain the first solution. The stirring speed can be 100rpm-400rpm.
[0059] After obtaining the first solution, it can be aged for 10-24 hours; after aging, it can be filtered and dried to obtain the aforementioned ternary precursor.
[0060] The technical effects of the above-mentioned cathode material will be explained below through some experimental and control groups:
[0061] Experimental group 1:
[0062] Material preparation: A solution of nickel sulfate, cobalt sulfate, and manganese sulfate was prepared in a molar ratio of 8:1:1. Sodium carbonate and ammonia were added to adjust the pH of the solution to 12. The solution was heated in a water bath at 60°C and stirred at 300 rpm for 1 hour. After aging for 12 hours, the mixture was vacuum filtered. The precipitate was washed clean and dried in an oven at 100°C for 12 hours to obtain the ternary precursor Ni. 0.8 Co 0.1 Mn 0.1(OH)2.
[0063] The above ternary precursor Ni 0.8 Co 0.1 Mn 0.1 (OH)2, LiOH, Al2O3, and Tb2O3 were mixed in a ball mill at 1000 rpm for 10 min in a molar ratio of 0.995:1.02:0.001:0.0015. The mixture was then placed in a muffle furnace and heated to 700 °C at 5 °C / min under a pure oxygen atmosphere and held for 10 h to obtain the positive electrode material (1).
[0064] Electrochemical test: The positive electrode material (1), conductive carbon black, and binder were ground into a slurry with an appropriate amount of NMP (N-methyl-2-Pyrrolidone) solvent at a mass ratio of 95:3:2.
[0065] The obtained slurry was coated onto Al foil with a 150 μm scraper and then dried in a vacuum drying oven at 100 °C for 12 h. The dried electrode was then compacted on a roller press with appropriate spacing and then sliced using a punching machine to obtain a positive electrode sheet with a diameter of 12 mm (1), which was weighed using an electronic balance.
[0066] The areal loading of the positive electrode (1) is 130-150 g / m². The negative electrode uses lithium metal as the counter electrode and 1 mol / L LiPF6 / ethylene carbonate (EC)-dimethyl carbonate (DMC) (EC to DMC mass ratio 1:1) as the electrolyte. The battery is assembled in a glove box and subjected to charge-discharge tests. The voltage range is 2.8–4.3 V, and the charge-discharge current density is 0.1 C.
[0067] DSC (Differential Scanning Calorimetry) test: 4 mg of positive electrode material (1) powder was taken for DSC test under nitrogen atmosphere, heating rate 5℃ / min, temperature range 25~500℃.
[0068] Experimental group 2:
[0069] Material preparation: A solution of nickel sulfate, cobalt sulfate, and manganese sulfate was prepared in a molar ratio of 8:1:1. Sodium carbonate and ammonia were added to adjust the pH of the solution to 12. The solution was heated in a water bath at 60°C and stirred at 350 rpm for 1 hour. After aging for 12 hours, the mixture was vacuum filtered. The precipitate was washed clean and dried in an oven at 100°C for 12 hours to obtain the ternary precursor Ni. 0.8 Co 0.1 Mn 0.1 (OH)2.
[0070] The above ternary precursor Ni0.8 Co 0.1 Mn 0.1 (OH)2, LiOH, Al2O3, and Sb2O3 were mixed in a ball mill at 1000 rpm for 10 min in a molar ratio of 0.99:1.02:0.002:0.003. Then the mixture was placed in a muffle furnace and heated to 700 °C at 5 °C / min under a pure oxygen atmosphere and held for 10 h to obtain the positive electrode material (2).
[0071] Electrochemical preparation: The positive electrode material (2), conductive carbon black, and binder were ground into a slurry with an appropriate amount of NMP solvent at a mass ratio of 95:3:2. The obtained slurry was coated onto Al foil with a 150 μm doctor blade and then dried in a vacuum drying oven at 100 °C for 12 h. The dried electrode sheet was compacted on a roller press with appropriate spacing, and then sliced using a punching machine to obtain a positive electrode sheet (2) with a diameter of 12 mm, which was weighed using an electronic balance.
[0072] The areal loading of the positive electrode (2) is 130-150 g / m2. The negative electrode uses lithium metal as the counter electrode and 1 mol / L LiPF6 / ethylene carbonate (EC)-dimethyl carbonate (DMC) (EC and DMC mass ratio 1:1) as the electrolyte. The battery is assembled in a glove box and subjected to charge-discharge tests. The voltage range is 2.8–4.3 V, and the charge-discharge current density is 0.1 C.
[0073] DSC test: Take 4mg of positive electrode material (2) powder for DSC test, nitrogen atmosphere, heating rate 5℃ / min, temperature range 25~500℃.
[0074] Experimental group 3:
[0075] Material preparation: A solution of nickel sulfate, cobalt sulfate, and manganese sulfate was prepared in a molar ratio of 8:1:1. Sodium carbonate and ammonia were added to adjust the pH of the solution to 12. The solution was heated in a water bath at 60°C and stirred at 300 rpm for 1 hour. After aging for 12 hours, the mixture was vacuum filtered. The precipitate was washed clean and dried in an oven at 100°C for 12 hours to obtain the ternary precursor Ni. 0.83 Co 0.12 Mn 0.05 (OH)2.
[0076] The above ternary precursor Ni 0.83 Co 0.12 Mn 0.05(OH)2, LiOH, Al2O3, and Tb2O3 were mixed in a ball mill at 1000 rpm for 10 min in a molar ratio of 0.985:1.02:0.0035:0.004. Then the mixture was placed in a muffle furnace and heated to 700 °C at 5 °C / min under a pure oxygen atmosphere and held for 10 h to obtain the positive electrode material (3).
[0077] Electrochemical test: The positive electrode material (3), conductive carbon black, and binder were ground into a slurry with an appropriate amount of NMP (N-methyl-2-Pyrrolidone) solvent at a mass ratio of 95:3:2.
[0078] The obtained slurry was coated onto Al foil with a 150 μm scraper and then dried in a vacuum drying oven at 100 °C for 12 h. The dried electrode was then compacted on a roller press with appropriate spacing and then sliced using a punching machine to obtain a positive electrode sheet with a diameter of 12 mm (3), which was weighed using an electronic balance.
[0079] The areal loading of the positive electrode (3) is 130-150 g / m2. The negative electrode uses lithium metal as the counter electrode and 1 mol / L LiPF6 / ethylene carbonate (EC)-dimethyl carbonate (DMC) (EC and DMC mass ratio 1:1) as the electrolyte. The battery is assembled in a glove box and subjected to charge-discharge tests. The voltage range is 2.8–4.3 V, and the charge-discharge current density is 0.1 C.
[0080] DSC (Differential Scanning Calorimetry) test: 4 mg of positive electrode material (3) powder was taken for DSC test under nitrogen atmosphere, heating rate 5℃ / min, temperature range 25~500℃.
[0081] Experimental group 4:
[0082] Material preparation: A solution of nickel sulfate, cobalt sulfate, and manganese sulfate was prepared in a molar ratio of 8:1:1. Sodium carbonate and ammonia were added to adjust the pH of the solution to 12. The solution was heated in a water bath at 60°C and stirred at 350 rpm for 1 hour. After aging for 12 hours, the mixture was vacuum filtered. The precipitate was washed clean and dried in an oven at 100°C for 12 hours to obtain the ternary precursor Ni. 0.83 Co 0.12 Mn 0.05 (OH)2.
[0083] The above ternary precursor Ni 0.83 Co 0.12 Mn 0.05(OH)2, LiOH, Al2O3, and Sb2O3 were mixed in a ball mill at 1000 rpm for 10 min in a molar ratio of 0.98:1.02:0.005:0.005. Then the mixture was placed in a muffle furnace and heated to 700 °C at 5 °C / min under a pure oxygen atmosphere and held for 10 h to obtain the positive electrode material (4).
[0084] Electrochemical preparation: The positive electrode material (4), conductive carbon black, and binder were ground into a slurry with an appropriate amount of NMP solvent at a mass ratio of 95:3:2. The obtained slurry was coated onto Al foil with a 150 μm doctor blade and then dried in a vacuum drying oven at 100 °C for 12 h. The dried electrode sheet was compacted on a roller press with appropriate spacing, and then sliced using a punching machine to obtain a positive electrode sheet (4) with a diameter of 12 mm, which was weighed using an electronic balance.
[0085] The areal loading of the positive electrode (4) is 130-150 g / m2. The negative electrode uses lithium metal as the counter electrode and 1 mol / L LiPF6 / ethylene carbonate (EC)-dimethyl carbonate (DMC) (EC and DMC mass ratio 1:1) as the electrolyte. The battery is assembled in a glove box and subjected to charge-discharge tests. The voltage range is 2.8–4.3 V, and the charge-discharge current density is 0.1 C.
[0086] DSC test: Take 4mg of positive electrode material (4) powder for DSC test, nitrogen atmosphere, heating rate 5℃ / min, temperature range 25~500℃.
[0087] Experimental group 5:
[0088] Material preparation: A solution of nickel sulfate, cobalt sulfate, and manganese sulfate was prepared in a molar ratio of 8:1:1. Sodium carbonate and ammonia were added to adjust the pH of the solution to 12. The solution was heated in a water bath at 60°C and stirred at 300 rpm for 1 hour. After aging for 12 hours, the mixture was vacuum filtered. The precipitate was washed and dried in an oven at 100°C for 12 hours to obtain the ternary precursor Ni. 0.8 Co 0.1 Mn 0.1 (OH)2.
[0089] The above ternary precursor Ni 0.8 Co 0.1 Mn 0.1 (OH)2, LiOH, Al2O3, and Sb2O3 were mixed in a ball mill at 1000 rpm for 10 min in a molar ratio of 0.995:1.02:0.00125:0.00125. The mixture was then placed in a muffle furnace and heated to 700 °C at 5 °C / min under a pure oxygen atmosphere and held for 10 h to obtain the positive electrode material (5).
[0090] Electrochemical preparation: The positive electrode material (5), conductive carbon black, and binder were ground into a slurry with an appropriate amount of NMP solvent at a mass ratio of 95:3:2. The obtained slurry was coated onto Al foil with a 150 μm scraper and then dried in a vacuum drying oven at 100 °C for 12 h. The dried electrode sheet was compacted on a roller press with appropriate spacing, and then sliced with a punching machine to obtain a positive electrode sheet (5) with a diameter of 12 mm, which was weighed using an electronic balance.
[0091] The areal loading of the positive electrode (5) is 130-150 g / m2. The negative electrode uses lithium metal as the counter electrode and 1 mol / L LiPF6 / ethylene carbonate (EC)-dimethyl carbonate (DMC) (EC to DMC mass ratio 1:1) as the electrolyte. The battery is assembled in a glove box and subjected to charge-discharge tests. The voltage range is 2.8–4.3 V, and the charge-discharge current density is 0.1 C.
[0092] DSC test: Take 4mg of positive electrode material (5) powder for DSC test, nitrogen atmosphere, heating rate 5℃ / min, temperature range 25~500℃.
[0093] Comparison Group 1:
[0094] Material preparation: A solution of nickel sulfate, cobalt sulfate, and manganese sulfate was prepared in a molar ratio of 8:1:1. Sodium carbonate and ammonia were added to adjust the pH of the solution to 12. The solution was heated in a water bath at 60°C and stirred at 300 rpm for 1 hour. After aging for 12 hours, the mixture was vacuum filtered. The precipitate was washed clean and dried in an oven at 100°C for 12 hours to obtain the ternary precursor Ni. 0.8 Co 0.1 Mn 0.1 (OH)2.
[0095] The above ternary precursor Ni 0.8 Co 0.1 Mn 0.1 (OH)2 and LiOH were mixed in a ball mill at a molar ratio of 1:1.02 at a speed of 1000 rpm for 10 min, and then placed in a muffle furnace and heated to 700℃ at a rate of 5℃ / min under a pure oxygen atmosphere and held for 10 h to obtain the positive electrode material (6).
[0096] Electrochemical testing: The positive electrode material (6), conductive carbon black, and binder were ground into a slurry with an appropriate amount of NMP solvent at a mass ratio of 95:3:2. The obtained slurry was coated onto Al foil with a 150 μm scraper and then dried in a vacuum drying oven at 100 °C for 12 h. The dried electrode sheet was compacted on a roller press with appropriate spacing, and then sliced with a punching machine to obtain a positive electrode sheet (6) with a diameter of 12 mm, which was weighed using an electronic balance.
[0097] The areal loading of the positive electrode (6) is 130-150 g / m². The negative electrode uses lithium metal as the counter electrode and 1 mol / L LiPF6 / ethylene carbonate (EC)-dimethyl carbonate (DMC) (EC and DMC mass ratio 1:1) as the electrolyte. The battery is assembled in a glove box and subjected to charge-discharge tests. The voltage range is 2.8–4.3 V, and the charge-discharge current density is 0.1 C.
[0098] DSC test: Take 4mg of positive electrode material (6) powder for DSC test, nitrogen atmosphere, heating rate 5℃ / min, temperature range 25~500℃.
[0099] Comparison Group 2:
[0100] Material preparation: A solution of nickel sulfate, cobalt sulfate, and manganese sulfate was prepared in a molar ratio of 8:1:1. Sodium carbonate and ammonia were added to adjust the pH of the solution to 12. The solution was heated in a water bath at 60°C and stirred at 300 rpm for 1 hour. After aging for 12 hours, the mixture was vacuum filtered. The precipitate was washed clean and dried in an oven at 100°C for 12 hours to obtain the ternary precursor Ni. 0.8 Co 0.1 Mn 0.1 (OH)2.
[0101] The above ternary precursor Ni 0.8 Co 0.1 Mn 0.1 (OH)2, LiOH, and Al2O3 were mixed in a ball mill at a speed of 1000 rpm for 10 min in a molar ratio of 0.99:1.02:0.005. Then, the mixture was placed in a muffle furnace and heated to 700 °C at a rate of 5 °C / min under a pure oxygen atmosphere and held for 10 h to obtain the positive electrode material (7).
[0102] Electrochemical testing: The positive electrode material (7), conductive carbon black, and binder were ground into a slurry with an appropriate amount of NMP solvent at a mass ratio of 95:3:2. The obtained slurry was coated onto Al foil using a 150 μm doctor blade and then dried in a vacuum drying oven at 100 °C for 12 h.
[0103] The dried electrode sheet was placed on a roller press with appropriate spacing and compacted. Then, it was sliced with a punching machine to obtain a positive electrode sheet with a diameter of 12 mm (7), and weighed with an electronic balance.
[0104] The areal loading of the positive electrode (7) is 130-150 g / m2. The negative electrode uses lithium metal as the counter electrode and 1 mol / L LiPF6 / ethylene carbonate (EC)-dimethyl carbonate (DMC) (EC and DMC mass ratio 1:1) as the electrolyte. The battery is assembled in a glove box and subjected to charge-discharge tests. The voltage range is 2.8–4.3 V, and the charge-discharge current density is 0.1 C.
[0105] DSC test: Take 4mg of positive electrode material (7) powder for DSC test, nitrogen atmosphere, heating rate 5℃ / min, temperature range 25~500℃.
[0106] Comparison Group 3:
[0107] Material preparation: A solution of nickel sulfate, cobalt sulfate, and manganese sulfate was prepared in a molar ratio of 8:1:1. Sodium carbonate and ammonia were added to adjust the pH of the solution to 12. The solution was heated in a water bath at 60°C and stirred at 300 rpm for 1 hour. After aging for 12 hours, the mixture was vacuum filtered. The precipitate was washed clean and dried in an oven at 100°C for 12 hours to obtain the ternary precursor Ni. 0.8 Co 0.1 Mn 0.1 (OH)2.
[0108] The above ternary precursor Ni 0.8 Co 0.1 Mn 0.1 (OH)2, LiOH, and Sb2O3 were mixed in a ball mill at 1000 rpm for 10 min in a molar ratio of 0.985:1.02:0.0075. The mixture was then placed in a muffle furnace and heated to 700 °C at 5 °C / min under a pure oxygen atmosphere and held for 10 h to obtain the cathode material (8).
[0109] Electrochemical testing: The positive electrode material (8), conductive carbon black, and binder were ground into a slurry with an appropriate amount of NMP solvent at a mass ratio of 95:3:2. The obtained slurry was coated onto Al foil with a 150 μm doctor blade and then dried in a vacuum drying oven at 100 °C for 12 h.
[0110] The dried electrode sheet was placed on a roller press with appropriate spacing and compacted. Then, it was sliced with a punching machine to obtain a positive electrode sheet with a diameter of 12 mm (8), and weighed with an electronic balance.
[0111] The areal loading of the positive electrode (8) is 130-150 g / m². The negative electrode uses lithium metal as the counter electrode and 1 mol / L LiPF6 / ethylene carbonate (EC)-dimethyl carbonate (DMC) (EC and DMC mass ratio 1:1) as the electrolyte. The battery is assembled in a glove box and subjected to charge-discharge tests. The voltage range is 2.8–4.3 V, and the charge-discharge current density is 0.1 C.
[0112] DSC test: Take 4mg of positive electrode material (8) powder for DSC test, nitrogen atmosphere, heating rate 5℃ / min, temperature range 25~500℃.
[0113] Comparison Group 4
[0114] Material preparation: A solution of nickel sulfate, cobalt sulfate, and manganese sulfate was prepared in a molar ratio of 8:1:1. Sodium carbonate and ammonia were added to adjust the pH of the solution to 12. The solution was heated in a water bath at 60°C and stirred at 300 rpm for 1 hour. After aging for 12 hours, the mixture was vacuum filtered. The precipitate was washed clean and dried in an oven at 100°C for 12 hours to obtain the ternary precursor Ni. 0.8 Co 0.1 Mn 0.1 (OH)2.
[0115] The above ternary precursor Ni 0.8 Co 0.1 Mn 0.1 (OH)2, LiOH and Nb2O5 were mixed in a ball mill at 1000 rpm for 10 min in a molar ratio of 0.98:1.02:0.001. Then the mixture was placed in a muffle furnace and heated to 700 °C at 5 °C / min under a pure oxygen atmosphere and held for 10 h to obtain the positive electrode material (9).
[0116] Electrochemical testing: The positive electrode material (9), conductive carbon black, and binder were ground into a slurry with an appropriate amount of NMP solvent at a mass ratio of 95:3:2. The obtained slurry was coated onto Al foil using a 150 μm doctor blade and then dried in a vacuum drying oven at 100 °C for 12 h.
[0117] The dried electrode sheet was placed on a roller press with appropriate spacing and compacted. Then, it was sliced with a punching machine to obtain a positive electrode sheet with a diameter of 12 mm (9), and weighed with an electronic balance.
[0118] The areal loading of the positive electrode (9) is 130-150 g / m². The negative electrode uses lithium metal as the counter electrode and 1 mol / L LiPF6 / ethylene carbonate (EC)-dimethyl carbonate (DMC) (EC and DMC mass ratio 1:1) as the electrolyte. The battery is assembled in a glove box and subjected to charge-discharge tests. The voltage range is 2.8–4.3 V, and the charge-discharge current density is 0.1 C.
[0119] DSC test: Take 4mg of positive electrode material (9) powder for DSC test, nitrogen atmosphere, heating rate 5℃ / min, temperature range 25~500℃.
[0120] Table 1 compares the electrochemical and thermal performance of experimental groups 1-5 and control groups 1-4:
[0121] Table 1:
[0122]
[0123]
[0124] The table shows that the retention rate after 100 cycles and the peak temperature of DSC thermal decomposition in experimental groups 1-5 are higher than those in control groups 1-4.
[0125] As shown in Table 1, the embodiments of the present invention introduce Al and Sb elements into the ternary cathode to achieve bulk and surface co-doping, thereby obtaining a cathode material with a core-shell structure. Bulk doping of Al introduces Al-O bonds with higher bond energy, thus improving the bulk structural stability of the material. The introduction of Sb can adjust the microstructure of the material, alleviate stress concentration caused by the shrinkage and expansion of phase change materials, and suppress the generation of microcracks. Furthermore, the enrichment of Sb on the material surface can stabilize the lattice oxygen on the cathode surface, suppress surface structure decay, and improve the thermal stability of the material in the high delithiation state.
[0126] Finally, it should be noted that in this document, relational terms such as "first" and "second" are used only to distinguish one entity or operation from another, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Furthermore, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, or article that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, or article. Without further limitations, an element defined by the phrase "comprising one..." does not exclude the presence of other identical elements in the process, method, or article that includes said element.
[0127] The foregoing has provided a detailed description of the positive electrode of a ternary lithium-ion battery, a ternary lithium-ion battery, and a method for preparing the positive electrode of a ternary lithium-ion battery. Specific examples have been used to illustrate the principles and implementation methods of the present invention. The descriptions of the above embodiments are only for the purpose of helping to understand the method and core ideas of the present invention. At the same time, for those skilled in the art, there will be changes in the specific implementation methods and application scope based on the ideas of the present invention. Therefore, the content of this specification should not be construed as a limitation of the present invention.
Claims
1. A positive electrode for a ternary lithium-ion battery, characterized in that, The positive electrode includes: Li (Ni a Co b Mr c ) x M 1-x O 2; Where 0.9≤x<1, a+b+c=1, M represents Al and Sb, and the molar ratio of Al to Sb is 0.7-1.
5.
2. A ternary lithium-ion battery, characterized in that, The positive electrode of the ternary lithium-ion battery is the positive electrode as described in claim 1.
3. A method for preparing the positive electrode of a ternary lithium-ion battery, characterized in that, The preparation method includes: Ternary precursors are generated based on Ni, Co, and Mn sources; The ternary precursor was mixed with Li, Al, and Sb sources and then sintered to obtain the cathode material: Li(Ni) a Co b Mn c ) x M 1-x O2; where 0.9≤x≤1, a+b+c=1, M is Al and Sb, and the molar ratio of Al to Sb is 0.7-1.5; The positive electrode is prepared according to the positive electrode material of the positive electrode.
4. The preparation method according to claim 3, characterized in that, The process of generating a ternary precursor based on Ni, Co, and Mn sources includes: After uniformly mixing the Ni source, Co source, Mn source, precipitant and complexing agent, the pH was adjusted to 10-13, and the mixture was stirred at 50℃-80℃ for 1-2 hours to obtain the first solution. After aging the first solution for 10-24 hours, it is filtered and dried to obtain the ternary precursor.
5. The preparation method according to any one of claims 3-4, characterized in that, The Al source is either aluminum oxide or aluminum hydroxide.
6. The preparation method according to any one of claims 3-5, characterized in that, The Sb source is one of antimony oxide, antimony sulfate, or antimony acetate.
7. The preparation method according to any one of claims 3-5, characterized in that, The molar ratio of the ternary precursor Li:Al:Sb is: 1:(1-1.02):(0.001-0.0015):(0.0015-0.001)。 8. The preparation method according to claim 4, characterized in that, The precipitant is one of ammonium carbonate, ammonium bicarbonate, sodium carbonate, and sodium hydroxide; The complexing agent is one of ammonia, ammonium bicarbonate, and citric acid.
9. The preparation method according to any one of claims 3-8, characterized in that, The Ni source is one of nickel nitrate, nickel sulfate, and nickel chloride; The Co source is one of cobalt nitrate, cobalt sulfate, and cobalt chloride; The Mn source is one of manganese nitrate, manganese sulfate, or manganese chloride.
10. The preparation method according to any one of claims 3-9, characterized in that, The Li source is one of lithium hydroxide, lithium carbonate, and lithium acetate.
